Influence of Polymer Additives on the Efficiency and Stability of Ambient‐Air Solution‐Processed Planar Perovskite Solar Cells. Issue 12 (23rd October 2018) - Wang, Deng; Zhang, Lei; Deng, Kaiming; Zhang, Weina; Song, Jing; Wu, Jihuai; Lan, Zhang
Abstract: It is challenging to fabricate efficient and stable perovskite solar cells (PSCs) in ambient air conditions without special controlled humidity. Here, we report a facile polymer additive route to overcome the problem. We find that the polyvinyl butyral (PVB) and polyvinyl alcohol (PVA) additives can both obviously enhance the quality of the perovskite films compared with the pristine one. Especially, the perovskite film with PVB additive shows clearer improved quality because of the formation of larger crystal grains which can go from bottom to top and smoother surface with the lower root‐mean‐square roughness of 23.4 nm than that of the one with PVA additive (45.6 nm). The improved quality of the perovskite films with PVB additive contributes to better photovoltaic performance and long‐term stability of the devices. The PSCs with PVB additive can achieve a champion power conversion efficiency (PCE) of 19.10 % and a small hysteresis index of 0.039, which are both better than those of the pristine ones (15.14 % and 0.148, respectively). Furthermore, the PSC with PVB additive can maintain a relatively high PCE of 12.43 % after being stored in a humid ambient air condition without any encapsulation, whereas the pristine one drops to a very low PCE of 5.18 %. This work demonstrates the valuable PVB additive route for developing efficient and stable PSCs in ambient air conditions. Abstract : We report a facile polymer additive route to prepare potentially available efficient and stable planar PSCs.The polyvinyl butyral (PVB) and polyvinyl alcohol (PVA) additives can obviously enhance the quality of perovskite films. Especially, the perovskite film with PVB additive shows clearer improved quality because of the formation of larger crystal grains which can go from bottom to top and smoother surface than that of the one with PVA additive. Furthermore, the device with PVB additive shows superior photovoltaic performance, reduced hysteresis and greatly improved air stability.